2008
DOI: 10.1002/app.29138
|View full text |Cite
|
Sign up to set email alerts
|

Cracking in poly(trimethylene terephthalate) spherulites

Abstract: The crack behavior of poly(trimethylene terephthalate) spherulites was studied mainly by polarizing optical microscopy, along with scanning electron microscopy (SEM) and atomic force microscopy (AFM). In addition to the effects of temperature and constraining substrate, another important factor, film thickness, on the formation of crack was first put forward and investigated. The emergence of the first crack occurred at 120 C during cooling after crystallization at 190 C for the sample with a thickness of 31.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Poly(trimethylene terephthalate) (PTT), being a much tougher polymer than PLLA or PHB, shows cracks only in more severe circumstances. Yao and Yang [ 44 ] studied cracking in poly(trimethylene terephthalate) (PTT) spherulites grown between two substrates, crystallized at T c = 190 °C and cooled to lower temperatures or ambient (120, 90, 40 °C). They reported that PTT spherulites grown between two polyimide and two Teflon sheets showed no cracks, but PTT film grown between two glass sheets lubricated with silicon oil displayed reduced number of cracks but did not totally eliminate cracks.…”
Section: Cracks In Poly(trimethylene Terephthalate) (Ptt) Ring-banmentioning
confidence: 99%
“…Poly(trimethylene terephthalate) (PTT), being a much tougher polymer than PLLA or PHB, shows cracks only in more severe circumstances. Yao and Yang [ 44 ] studied cracking in poly(trimethylene terephthalate) (PTT) spherulites grown between two substrates, crystallized at T c = 190 °C and cooled to lower temperatures or ambient (120, 90, 40 °C). They reported that PTT spherulites grown between two polyimide and two Teflon sheets showed no cracks, but PTT film grown between two glass sheets lubricated with silicon oil displayed reduced number of cracks but did not totally eliminate cracks.…”
Section: Cracks In Poly(trimethylene Terephthalate) (Ptt) Ring-banmentioning
confidence: 99%
“…[25] The cracks are formed when samples are cooled from T c to low temperatures, and normally observed in polymers which can form relatively large spherulites. [26] Cracks within polyhydroxybutyrate, [27][28][29] poly(trimethylene terephthalate), [30] and PLLA [26] spherulites have already been observed. The formation of cracks can be affected by temperature, substrate, and film thickness.…”
Section: Crack Formationmentioning
confidence: 99%
“…Except for pure PTT sample, obvious cracked spherulites morphologies were observed in all PTT/ZnO nanocomposite samples. Similar phenomenon in pure PTT had been discussed in our previous work . Cracked spherulites morphology in pure PTT was hugely influenced by crystallization process, sample thickness, crystallization substrate, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Similar phenomenon in pure PTT had been discussed in our previous work. [32] Cracked spherulites morphology in pure PTT was hugely influenced by crystallization process, sample thickness, crystallization substrate, and so on. For PTT/ZnO nanocomposite prepared by dual in situ polymerization, cracked spherulites morphologies were really complicated to discuss.…”
Section: Crystalline Morphologymentioning
confidence: 99%